Positioning pharmacists' roles in primary health care: a discourse analysis of the compensation plan in Alberta, Canada. Issue 1 (December 2017) - Hughes, Christine; Breault, Rene; Hicks, Deborah; Schindel, Theresa
Abstract Background A comprehensive Compensation Plan for pharmacy services delivered by community pharmacists was implemented in Alberta, Canada in July 2012. Services covered by the Compensation Plan include care planning services, prescribing services such as adapting prescriptions, and administering a drug or publicly-funded vaccine by injection. Understanding how the Compensation Plan was framed and communicated provides insight into the roles of pharmacists and the potential influence of language on the implementation of services covered by the Compensation Plan by Albertan pharmacists. The objective of this study is to examine the positioning of pharmacists' roles in documents used to communicate the Compensation Plan to Albertan pharmacists and other audiences. Methods Publicly available documents related to the Compensation Plan, such as news releases or reports, published between January 2012 and December 2015 were obtained from websites such as the Government of Alberta, Alberta Blue Cross, the Alberta College of Pharmacists, the Alberta Pharmacists' Association, and the Blueprint for Pharmacy. Searches of the Canadian Newsstand database and Google identified additional documents. Discourse analysis was performed using social positioning theory to explore how pharmacists' roles were constructed in communications about the Compensation Plan. Results In total, 65 publicly available documents were included in the analysis. The Compensation Plan was put forward as a framework for payment for professional services and formal legitimization of pharmacists' changing professional roles. The discourse associated with the Compensation Plan positioned pharmacists' roles as: (1) expanding to include services such as medication management for chronic diseases, (2) contributing to primary health care by providing access to services such as prescription renewals and immunizations, and (3) collaborating with other health care team members. Pharmacists' changing roles were positioned in alignment with the aims of primary health care. Conclusions Social positioning theory provides a useful lens to examine the dynamic and evolving roles of pharmacists. This study provides insight into how communications regarding the Compensation Plan in Alberta, Canada positioned pharmacists' changing roles in the broader context of changes to primary health care delivery. Our findings may be useful for other jurisdictions considering implementation of remunerated clinical services provided by pharmacists.